2019
DOI: 10.1111/jocn.14918
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of laboratory results between two blood samplings: Venipuncture versus peripheral venous catheter—A systematic review with meta‐analysis

Abstract: Aims and objectives To compare the results of haematology, blood chemistry and coagulation tests between two blood sampling methods via venipuncture and peripheral venous catheter. Background Laboratory results of the previous studies on blood sampling methods through peripheral venous catheter versus venipuncture are inconsistent. Therefore, it is necessary to better understand the discrepancies between the two blood sampling methods and to provide evidence for practice. Design Systematic literature review an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…As a result of differences in how studies were conducted, mixed findings on the efficacy of sampling blood from PIVCs have not produced strong evidencebased practice recommendations. Systematic reviews by Coventry et al (2019) and Jeong et al (2019) found equivalence in the accuracy of blood results, but outlined limitations with the studies and recommended further research into the practice of obtaining blood samples from PIVCs. Awareness of policy guidelines across Australia on the practice, and the prevalence of obtaining blood samples from PIVCs, has not been examined in a national survey.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As a result of differences in how studies were conducted, mixed findings on the efficacy of sampling blood from PIVCs have not produced strong evidencebased practice recommendations. Systematic reviews by Coventry et al (2019) and Jeong et al (2019) found equivalence in the accuracy of blood results, but outlined limitations with the studies and recommended further research into the practice of obtaining blood samples from PIVCs. Awareness of policy guidelines across Australia on the practice, and the prevalence of obtaining blood samples from PIVCs, has not been examined in a national survey.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some health services have guidelines against the practice of blood sampling from PIVC, and others do not have guidelines (Jacob et al, 2020). Systematic literature reviews have been undertaken to find existing evidence in relation to the safety and accuracy of drawing blood from PIVC (Coventry et al, 2019;Jeong et al, 2019;Lesser et al, 2020). The reviews found the practice of taking blood from PIVCs was safe (Jeong et al, 2019;Lesser et al, 2020) or recommended further research into the practice (Coventry et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Yet the evidence around the use of PIVC for blood sampling is unclear. A systematic review by Jeong et al (2019) found that sampling from PIVC or venepuncture is likely to provide equivalent levels of accuracy for the most commonly used tests. This is in line with a systematic review by Coventry and colleagues (2019) (Davies et al, 2019).…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…A systematic review by Jeong et al. (2019) found that sampling from PIVC or venepuncture is likely to provide equivalent levels of accuracy for the most commonly used tests. This is in line with a systematic review by Coventry and colleagues (2019) that found limited evidence to suggest that use of PIVC for blood sampling contributed to decreased accuracy, but that PIVC use may lead to increased haemolysis rates.…”
Section: Introductionmentioning
confidence: 99%